Consumer Attitude towards Genetically Modified Foods of a Selected Community in A Grama Niladhari Division of Kalutara District, Sri Lanka - Wickramasinghe, W.T.R.; Dhananjani, M.A.; Pathirage, D.C.; Ransika, E.A.M.; Yuwanthika, B.A.S.; Kulathunga, H.; Ubhayawardana, D.L.N.L. (My University, 2022)
Introduction: Genetically modified foods (GM) consist of plants and animals which has experienced gene manipulation. Most of the time, consumers have no idea that their food has been modified. The reported negative results of consuming GM foods are food allergies, and colon, breast, and lung cancers. The food consumption rate and associated diseases are increased due to the considerable population in Kalutara District. Therefore, this study determined people's attitude towards GM foods in the Kotigamgoda Grama Niladhari Division in Kalutara District, Sri Lanka. Objective: To determine the consumer attitude towards GM foods of a selected community in a selected Grama Niladhari Division of Kalutara, Sri Lanka. Methods: This study is a descriptive cross-sectional study. Researcher-developed validated selfadministered questionnaire consisting of socio-demographic data, and attitudes about GM foods were used. The survey was carried out on 250 respondents (sample size, n= N/1 + N*e2 ) using a systematic random sampling method. Among 250 respondents, majority were females (n= 153, 61.2%) and had higher education (n=81, 32.4%). Data were analyzed for descriptive statistics and Pearson’s chi-square method using SPSS version 25. Attitudes were graded high, low, and moderate using Bloom’s cut-off points. Results: The majority of the respondents 108 (43.2%) had low attitude, followed by moderate attitude of 83 (33.2%), and high attitude of 59 (23.6%). A significant association was identified between noncommunicable disease conditions and the attitudes of the respondents (p value<0.05). Conclusions: Consumer attitudes toward GM foods were low, especially related to health risks, purchasing decisions of GM foods, non-GM foods, and rules which regulate GM foods. Providing more education regarding GM foods will increase the attitude towards GM foods among people. Further studies are necessary to confirm attitudes towards GM foods in various communities and the relationship between GM foods and non-communicable diseases in Sri Lanka.
Keywords: Consumers; Attitude; Genetically Modified Foods